Crying for my Father’s Home: Poetics of Loss of the Father’s Land and Mourning in John Edgar Wideman’s The Cattle Killing - AZON, Sènakpon Adelphe Fortuné (My University, 2019)
In a disjointed narrative drunkenness that straddles oneiric language, apocalyptic vaticinations, and alcoholic delirium, the narrative of the young itinerant preacher in John Edgar Wideman’s Cattle Killing unfurls. The narrative purports to be clear in launching the young lover into an asymptotic search for his soul mate who is nothing but a spirit akin to ogbanji, successively incarnated in deified women who experience an elusive existence and a tragic death. However, it fails to dispel, in readers, a deep doubt as to the intrinsic symbolism of this soul mate, and, finally, dissuades them that it is an ordinary love story. The Cattle Killing quilts the story of the deadly prophecy of Nongqawuse, decisive in the colonial conquest of the Xhosas in Southern Africa, into that of the epidemic yellow fever in Philadephia, and plunges the protagonist into a melancholic quest on which African people’s awakening is premised. Voudoun esthetics, Lacan’s theory of desire, and Genettian narratology constitute the major paradigm on which the textual analysis of this paper proceeds. Its aim is to highlight the narrative devices by which the poetics of affliction, melancholy and regret is activated in the work, with the aim of echoing its call for the improvement of the black people’s condition in the United States and all over the world Résumé Dans une ivresse narrative désarticulée à cheval entre langage onirique, vaticinations apocalyptiques et délire d’ébriété, s’enchevêtre la narration des errances du jeune prêcheur itinérant anonyme du Massacre du bétail de John Edgar Wideman. Si le récit se veut clair dans son intention de lancer le jeune amoureux dans une quête asymptotique de son âme sœur qui n’est rien d’autre qu’un esprit similaire à ogbanji, celui-ci s’incarnant tour à tour dans des femmes déifiées dont l’existence est élusive et le décès tragique, il ne réussit néanmoins pas à dissiper, chez le lecteur, un doute profond quant à la symbolique même de cette âme sœur, et le dissuade, enfin, qu’il s’agit d’une histoire d’amour ordinaire. Le Massacre du bétail entrelace le récit de la prophétie meurtrière de Nongqawuse qui fut déterminante dans la conquête coloniale des Xhosas en Afrique Australe et le récit de la fièvre épidémique de Philadelphie, et, dans le même temps, plonge le protagoniste dans une quête mélancolique qui se veut prémices indispensables à une prise de conscience des peuples noirs. L’esthétique voudoun, la théorie du désir de Lacan et la narratologie généttienne constituent la principale toile de fond sur laquelle s’élabore l’analyse textuelle du présent article. Il vise à mettre en exergue le mécanisme par lequel procède la poétique de l’affliction, de la mélancolie et du regret dans l’œuvre, afin de faire écho à son appel à l’amélioration de la condition noire aux Etats-Unis et partout dans le monde.
Keywords: Erzulie; Affliction; Desire; Africa; Quest; Nongqawuse